Studi Keanekaragaman JamurKayu Makroskopis di EduparkUniversitas Muhammadiyah Surakarta - Suryani, Titik; Istiqomah, Rizqi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Edupark is an educational park owned by Muhammadiyah University of Surakarta located at an altitude of 105 asl, an average temperature of 30º C and also width an area of 47.065 m². The purpose of this research  was  to determine the kinds  of wood mushroom (macroscopics) in Edupark UMS. This explorative  research used a purposive sampling method and  wood mushroom sample was taking by  whenever find and was not do again if they found the same wood mushroom. The next stage,  the wood mushrooms were inventory and  identified by  using the identification  book of The Pocket Guide to Mushrooms and Field Guide to Common macrofungi in Eastern Forests and Their Ecosystem Functions and  qualitative description  analysis. The research result obtained 27 species of wood mushroom in 5 families, namely Polyporaceaefamily  (13 species), Agaricaceae family  (11 species), Auriculariaceae family (1 species), Helvellaceae family (1 species), and Helotiaceae family (1 species).